Cover Picture: Antivirulence Isoquinolone Mannosides: Optimization of the Biaryl Aglycone for FimH Lectin Binding Affinity and Efficacy in the Treatment of Chronic UTI (ChemMedChem 4/2016). (February 2016) - Jarvis, Cassie; Han, Zhenfu; Kalas, Vasilios; Klein, Roger; Pinkner, Jerome S.; Ford, Bradley; Binkley, Jana; Cusumano, Corinne K.; Cusumano, Zachary; Mydock‐McGrane, Laurel; Hultgren, Scott J.; Janetka, James W.
Abstract : The front cover picture shows the X‐ray structure of two bacterial FimH antagonists, 4′‐(α‐d ‐mannopyranosyloxy)‐ N 3, N 5, 3′‐trimethyl‐[1, 1′‐biphenyl]‐3, 5‐dicarboxamide (7, green) and 4′‐(α‐d ‐mannopyranosyloxy)‐[1, 1′‐biphenyl]‐3‐carboxylic acid methyl ester (2, yellow), bound to the lectin domain. These α‐mannosides block the adhesion and invasion of UPEC to host cells in urinary tract infections (UTIs) with low nm affinities. Optimized mannoside7 was rationally designed using the structure of2 . Capitalizing on the improved interactions of7 with FimH, especially with Y48 and R98, 7‐[4‐(α‐d ‐mannopyranosyloxy)‐3‐methylphenyl]‐1(2 H )‐isoquinolinone (22 ), shown centered at the bottom, was rationally designed. This restricts the amide into the bound conformation. N‐substituted analogs hold a 30‐fold increase in potency derived from higher FimH affinity. Lead mannoside22 displayed the best oral bioavailability, compound exposure, and efficacy when tested in a mouse model of UTI and represents a promising new antivirulence candidate drug for UTI. More information can be found in the Communication by James W. Janetka et al. onpage 367 in Issue 4, 2016 (DOI:10.1002/cmdc.201600006 ).